Acknowledgment - Mohamad Abdun Nasir (Ulumuna, 2017)
Ulumuna Journal of Islamic Studies would like to acknowledge the contribution of the following scholars in reviewing the articles published in Ulumuna Vol. 20, No. 1 (June) 2016.   Abdul Fattah : State Islamic Institute (IAIN) Mataram, Indonesia Ahmad Najib Burhani : Lembaga Ilmu Pengetahuan Indonesia (LIPI), SCOPUS ID = 45861172800 Ahmad Sahidah : Universiti Utara Malaysia (UUM) Al Makin : Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia, SCOPUS ID = 38162109000 Fachrizal Halim : University of Saskatchewan, Canada, SCOPUS ID = 55530741400 Hans Abdiel Harmakaputra : Boston College, Chestnut Hill, United States, SCOPUS ID: 57190061513 Zakiyuddin Baidhawy : State Institute of Islamic Studies (IAIN) Salatiga, Indonesia, SCOPUS ID: 26037319900